Oud neg.nr. 72769, 72536-72538, 72472-72473. 'Amsterdamse politie en politie bij verkeersexamen' - Haas, Joh. de, (1972)
Oud neg.nr. 72769, 72536-72538, 72472-72473. 'Amsterdamse politie en politie bij verkeersexamen'.